The Effectiveness of Geography Learning in The 2013 Curriculum - Dian Rakhmasari; Inti Nur Tirta; Iqnia Fajril Wahida; M. Fajar Septarianto; Shandy Choirul Fatah; Yunia Dwi Karina (Basic and Applied Education Research Journal, 2020)
This research aims to determine the effectiveness of the use of the 2013 curriculum in geography subjects. Data analysis techniques were used quantitative descriptive analysis as to analyze the data in ways that describe or depict the data that has been obtained. This study was used data collection techniques by distributing questionnaires, interviews and documentation. Data analysis uses descriptive data analysis techniques . The results showed that the use of the 2013 curriculum was still not going well. The effectiveness of learning with the application of the 2013 curriculum in geography is still needed a lot of review and adaptation of characteristics.